Evaluation of the effect of Azospirillum brasilense inoculation on arabic coffee seedlings - Franco Júnior, Kleso Silva; Barbosa, Camila Karen Reis; Silva, Leonardo Caixeta da (Coffee Science - ISSN 1984-3909, 2020)
In fabaceae, Azospirilum is used in association with Rhizobium bacteria to promote biological nitrogen fixation, making the plant tolerant to water stress and resulting in better nutrient utilization, obtaining a plant more productive and vigorousand increase roots for better nutrient uptake by the plant. However, there are no studies using coinoculation in Coffee. The objective of the study was to evaluate the effect of different doses of A. brasilense on the development of coffee seedlings. The experiment was carried out in Machado, southern Minas Gerais. The experimental design was completely randomized (DIC), with five treatments and nine replications, totaling 45 experimental plots. The experimental unit consisted of pots of 12 liters of capacity with a substrate composed of 70% soil and 30% of tanned manure and a coffee seedling of cultivar Catuaí Vermelho IAC 144. Treatments were composed with different doses (0, 0.75, 1.5, 2.25 and 3.0 mL) of Azospirillum brasilense inoculant from the Micro-Chemistry laboratory, Azofix®, having Ab-V5 strains, 1 x 108 cfu. mL-1 viable cells per mL. From stage V7, the seedlings received eight applications with a seven-day interval. The applying was done in the late afternoon, under favorable environmental conditions, using a hand sprayer. Evaluations were performed 150 days after the first application. The variables evaluated were shoot height (ALT) (cm); shoot fresh matter (MFPA) (g); root fresh matter (MFR) (g); leaf fresh matter (MFF) (g); stem diameter (DIA)(mm) and pivoting root length (CRP) (cm). It is concluded that the inoculation of coffee seedlings with bacteria of the species Azospirillum brasilense promotes greater growth of the pivoting root as well as the fresh matter of the whole root system of coffee seedlings. Key words: Coffea arabica; Seedlings production; Symbiosis.